Utilizing Artificial Intelligence (AI) Technology to support MSMEs businesses: ChatGPT - Dida Nurhaida*; Ellyana Amran; Erie Riza Nugraha; Amirul Faiz Bin Osman; Aqilah Nazla Shafira (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
In the digital age, MSMEs must continuously innovate and devise impactful marketing strategies to stay competitive in the midst of intense business competition. Embracing digital marketing is crucial, but it comes with challenges, particularly in creating compelling promotional texts. To address this, the author assisted “Kedai Uni Im”, a MSMEs specializing in Minang Kabau delicacies, by utilizing ChatGPT for marketing content creation. Training and mentoring were provided as part of the science and technology diffusion method. The study's results indicate positive outcomes, including successful implementation of promotional text designs using ChatGPT, increased confidence in creating social media content, and more regular updates on social media platforms. Going forward, it is recommended to explore further benefits of ChatGPT for supporting MSMEs. Additionally, considering the significance and benefits of using ChatGPT for MSMEs, these materials can be replicated and shared broadly with other MSMEs players.